History of the Bukhara branch of the Azov-Don commercial bank - B. A. Alimdjanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article investigates foundations of work and functions of the Bukhara branch of the Azov-Don commercial bank. In soviet historiography banks were considered as colonialism tools (both Western and Russian). On the basis of archive data the author proves that finance institutions of the Russian Empire took into account the local specificity and stimulated production of export-oriented goods. The author uses inter-bank correspondence, annual reports of the branch director and materials of the Bukhara branch audit. For the first time active and passive bank transactions were researched, expenses and incomes of the bank were analyzed and personnel of the bank was studied. The author, in contrast to soviet and post-soviet researchers thinks that banks were not monopolists in economy of the Middle East. The Azov-Don bank had got a broad network of branches (4 branches) in the Middle East region. It tried to take in hand the export of cotton and fruit but could not become a monopolist in economic life of Turkestan. The principle cause of ‘failure’ according to the author was the adjustment of the bank to real economic relations in the Turkestan Governorship-General and khanates. Modernization of Central Asia economy, according to banks implied financing of export crops and intermediary between the metropolitan country and periphery. ‘Colonial’ periphery seemed to be an appealing field for investment and super-profit, but speculative nature of Turkestan economy stopped banks’ development. As a result economic modernization of the Middle East slowed down and opened the way to the soviet experiment.